Prevalence and Clinical Relevance of Exon 2 Deletion of COMMD1 in Bedlington Terriers in Korea. (11th October 2016) - Kim, Y.G.; Kim, S.Y.; Kim, J.H.; Lee, K.K.; Yun, Y.M.
Abstract : Background: Deletion of exon 2 of copper metabolism domain containing 1 ( COMMD1 ) results in copper toxicosis in Bedlington terriers (CT‐BT). Objectives: This study was conducted to identify the prevalence and clinical relevance of the COMMD1 mutation in Bedlington terriers in Korea. Animals: A total of 105 purebred Bedlington terriers (50 males, 55 females) from the kennels and pet dog clubs in Korea were examined during the period 2008–2013. Methods: A multiplex PCR was carried out to detect exon 2 deletion of COMMD1 . Clinical analysis was performed on each genetic group, and clinical status of the dogs was followed up to estimate survival probability. Results: Of the 105 samples, 52 (49%) were wild‐type homozygote, 47 (45%) were heterozygote, and 6 (6%) were mutant‐type homozygote. Plasma alanine aminotransferase (ALT) activity was increased in the mutant‐type homozygous group >2 years of age ( P < .0001). The survival probability of 6 mutant‐type homozygotes surviving 2.5 years was 0.67, and 4 years was 0.5. Conclusions and Clinical Importance: Results show the prevalence and clinical relevance of exon 2 deletion of COMMD1 and could help establish a structured selective breeding program to prevent CT‐BT in Korea.